Decarboxylation efficiency of carboxylic acids as ligands of metal oxide nanocluster resists upon γ-ray irradiation. (1st March 2022) - Otsuka, Tomoe; Muroya, Yusa; Ikeda, Takuya; Komuro, Yoshitaka; Kawana, Daisuke; Kozawa, Takahiro
Abstract: Metal oxide nanocluster resists have recently attracted considerable attention for use in extreme ultraviolet lithography. To obtain sophisticated guidelines for material design, it is necessary to understand well the radiation-induced chemical reaction scheme including the insolubilization mechanism. In this study, the production of CO2, which is considered to be one of the end products of treatment with an ionizing radiation, was investigated for eight types of carboxylic acid under various conditions using γ -rays ( 60 Co) as a radiation source. The amount of CO2 produced was measured by gas chromatography. G CO2 (/100 eV), which indicates decarboxylation efficiency, was evaluated. CO2 was generated through electron addition, hole transfer, and hydroxyl radical addition to the molecular and ionic forms of carboxylic acids. The dependences of G CO2 on reaction partners were clarified. The dependences of G CO2 on the molecular structure and dissociative state of carboxylic acids were also clarified.